EXPLORING THE NEXUS BETWEEN SUSTAINABLE CONSUMPTION BEHAVIOR AND ORGANIC FOOD PURCHASE: A Comprehensive Review - Ismael, Awaz Shukri; Balogh, Péter (Applied Studies in Agribusiness and Commerce, 2023)
Recently, a remarkable increase in organic food consumption can been seen in both developed and developing countries. This research aims to identify the role of sustainable consumption behavior in purchasing organic food. The research problem has been formulated with several questions, most notably:  Does sustainable consumption behavior has a role in purchasing organic food? The relationship between sustainable consumption behavior and organic food has received a lot of attention in the literature. However, take a comprehensive approach to examine how sustainable consumption behavior might affect purchasing organic food? In order to examine the role of sustainable consumption behavior in buying organic food, this article proposes a framework that adopts a comprehensive approach. The author conducted a qualitative synthesis of the literature (Systematic Literature Review (PRISMA), including 43 articles, revealing several findings. One of them, is that sustainable consumption behavior positively and directly impacts buying organic food due to the health, environmental cognition, high quality, trust, and food safety. The second finding is that complex factors influence organic food buying behavior. For example, price is always likely to be an important factor for most customers. Moreover, the lack of knowledge about organic food is another factor affecting customers’ buying organic food.